SYAIR QAYS DAN NAYLA KARYA NIZAMI FANZAVI DENGAN NOVEL LAYLA MAJNUN KARYA NIZAMI GANJAVI (KAJIAN INTERTEKSTUALITAS) - Sri Rahayu (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2014)
This study aims to describe (1) QL equation with less poetic novel characterizations LM, (2) differences in QL with a novel lyric characterizations LM, (3) Application of trassformasi hipogram happens in it. This study used a qualitative approach. Theoretical basis used is intertekstualitas theory, comparative literature, the concept of transformation of poetry into the novel. Source of data used is poetry Qais and Laila (QL) and Novel Layla Majnun (LM).Based on the analysis, obtained the following results. (1) Equation characterizations and poetic novel QL LM was shown both in figures and in the poem QL LM novel, has the same character, almost the same (slight change), and different. Drawn character is the same character or Syed Syed Omri, or Majnun Qais, Laila or Layla, Laila's father, Ibn Salam, Nawfal, the mother of Qais, Laila and mother of the hunter. Almost the same figure depicted is the camel and the rider,crowsandowls,andSalimAmiri.(2) The difference with the novel characterizations QL LM poem, there are some differences in the nature of which changes in character, not dimunculkannya existing character in the poem to the novel, and the addition of new characters in the novel. The main character in the poem and the novel there are eighteen (18). Eighteen of these figures do not all appear in the novel. Figures that appear in the poem does not appear on the QL but LM is novel, an old Bedouin, crows, beggars, the camel drivers, and Salim Amiri. Being figures that appear in the novel is the LM, the owl, the horseman, the hermit, Zayd and Salim. Shrinking figure is an old Bedouin and beggars. Moderate leaders who experienced the addition of Zayd and the hermit. (3) application of the results obtained in the transformationhipogram twenty-three hipogram transformed in the novel. Based on the analysis in the discussion, the kind of transformation that occurs is five ekserp, two expansions, four modifications, five of the combined ekserp and modification, five of the combined expansion and modification, two conversions and modifications to be composite